The Effectiveness of Think Talk Write (TTW) Strategy in Teaching Writing Analytical Exposition Text Toward Students at SMAN 3 Medan - Suriani Simangunsong; Fenty Debora Napitupulu; Usman Sidabutar (Action Research Journal Indonesia (ARJI), 2025)
The background of this research is because students of SMA N 3 Medan have weak writing skills in analytical exposition texts due to lack of mastery of vocabulary, grammar, and writing structure. This study aims to examine the effectiveness of Think Talk Write (TTW) strategy in learning to write analytical exposition texts for students in grade XI of SMA Negeri 3 Medan. This study addresses the problem of students' difficulties in writing analytical exposition texts, particularly in organizing ideas and understanding text structures. The study employs a quantitative experimental method with a true experimental design, involving two groups: an experimental class taught using the TTW strategy and a control class taught through conventional methods. The research subjects were 72 class XI students of SMA Negeri 3 Medan who were divided into experimental and control groups. Data were collected through pre-tests and post-tests to measure students' writing performance. The research uses statistical data analysis techniques including normality tests, homogeneity tests, and t-tests. The findings show a significant improvement in the experimental group compared to the control group. The mean post-test score for the experimental group was 84.13, exceeding the control group's mean score of 71.2. In addition, the data collected for this study showed normal distribution. Based on the analysis conducted using the t-test, Tcount = 3.11 was obtained at a significant level of α = 5%, dk (n-1) = 14, so (15-1) = 14, so Ttable = 1.76. It can be concluded that Tcount > Ttable (3.11> 1.76).  The implication of the results of this study is that it shows that the Think Talk Write strategy can be widely adopted by English teachers as a more effective writing learning method than conventional methods to improve students' ability to write analytical exposition texts.